The circularity endeavour in the Ornamental Stone sector - Duarte de Almeida, I.; da Silva, Agostinho (26th Cambridge International Manufacturing Symposium Proceedings, 2022)
Circular economy (CE) initiatives are being taken in developed and developing countries and all economic sectors. At the heart of these initiatives is the transformation of the core supply chain management (SCM) processes that underlie current production/consumption patterns. A CE theoretical business model for the Portuguese Ornamental Stone sector (POSs) is presented. The qualitative analysis, applied to POS SMEs, identifies drivers and barriers, the balance of which represents current challenges in shaping the CE in these SMEs and across the supply chain. A CE optimal integration is presented. A cost-effectiveness perceptions analysis reveals cost-effective strategic plans that could be implemented to increase POSs circularity.